The Impact of Social Media on Teenagers' Mental Health: Study and Solutions - Khoiriyah, Lailatul (Maliki Interdisciplinary Journal, 2024)
Social media plays a significant role in the lives of modern teenagers; however, its negative impact on mental health is increasingly concerning. This article discusses the various effects of social media on teenagers' mental health, including heightened anxiety, depression, the risk of cyberbullying, sleep disturbances, and the Fear of Missing Out (FOMO) phenomenon. Based on research and case studies, excessive social media use has been shown to worsen teenagers' mental health. The article also offers solutions to mitigate the negative effects of social media, such as digital literacy education, time management, promoting positive content, and support from parents and schools. Through a comprehensive and integrated approach, teenagers are expected to use social media more wisely, minimizing its negative impact on mental health. This article aims to provide insights for teenagers, parents, and schools to understand and address the impact of social media on teenagers' mental health.